Roland Barthes Semiotic Analysis of the Interpretation of Body Shaming Issue in Tall Girl Movie - Fatimah, Nofia Ayu; Wirawanda, Yudha (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
Film is one of the media that is widely favored by the public, with visual art displayed by the public as if they can feel the continuity of the film with the reality of real life, as well as the action of body shaming in this film. Body shaming is an act of negatively commenting on body shape that can cause mental disorders and depression to the victim. One of the movies that discusses the action of body shaming is the movie "Tall Girl". This movie raises the issue of body shaming, in this case body shaming that occurs based on two factors, namely body shaming based on gender bias and body shaming based on physicality. The researcher examined the movie "Tall Girl" by using a descriptive qualitative method with semiotic theory from Roland Barthes in analyzing data about the impact and classification of body shaming actions. The purpose of this study is to provide an overview of how the issue of body shaming is interpreted, as well as to explain the impact and classification of body shaming actions. The results obtained are the issue of body shaming in this study are interpreted that this often happens but the perpetrators do not feel that they are doing body shaming themselves, they think that it is just a joke, the form of resistance to the action of body shaming in this film is to accept ourselves and not feel insecure about ourselves because everyone has advantages and disadvantages and no one is perfect.